THE PRACTICE OF POLYANDRY MARRIAGE IN WOLWAL VILLAGE IN THE PERSPECTIVE OF SOCIOLOGY OF ISLAMIC LAW - Hamsah, Yudi; Rahmi, Irma Nur (Institut Agama Islam Negeri (IAIN) Pontianak, 2023)
This study aims to find out how polyandry marriages are practiced in Wolwal Village, Alor Barat Daya District, Alor Regency, East Nusa Tenggara Province. This type of research is a type of qualitative research using field research methods, so that researchers go directly to the community and obtain valid data. The procedure of this research is data collection, data reduction, data presentation and the stage of verification or drawing conclusions. Based on the data collected then analyzed using a sociological normative approach, namely by assessing the facts or realities that exist in society or the values ??that are held in society, whether marriage is in accordance with the rules of Islamic teachings or actually deviates. The instruments used were observation, interviews, and documentation related to polyandry marriages in Wolwal Village. Based on the research results obtained, the researchers concluded that there were polyandry marriages in Wolwal Village. This marriage was caused on the basis of ignorance about the marriage procedure recommended by Islamic law and also other factors that increased within the perpetrator of the marriage so that the marriage took place. Meanwhile, in a sociological review of Islamic law, there is a prohibition in polyandry marriages due to the fact that in this marriage there will be defects in family relations or in society in general and not knowing the biological children of the couple.